2014
DOI: 10.1111/joor.12258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐level laser therapy in the treatment of TMDs: a meta‐analysis of 14 randomised controlled trials

Abstract: This study was designed to evaluate the efficacy of low-level laser therapy (LLLT) in the treatment of temporomandibular disorders (TMDs). We searched electronic databases and references lists of relevant articles, retrieved all of the published randomised controlled trials in regard to these issues and then performed a meta-analysis. Fourteen highly qualified RCTs reporting on a total of 454 patients, which evaluated the effectiveness of LLLT for patients suffering from TMDs were retrieved. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 28 publications
3
72
0
12
Order By: Relevance
“…Various treatments have been implemented for the treatment of TMD, including pharmacological therapy, psychological therapy, occlusal therapy, physical therapy, cognitive therapy, acupuncture therapy, and surgical interventions. [1114] In cases of myofascial pain, strategies often target muscle relaxation. [5] Acupuncture is a commonly used strategy for pain relief in these cases, in which an acupuncture needle or, more often, multiple needles are inserted at the appropriate acupuncture points.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatments have been implemented for the treatment of TMD, including pharmacological therapy, psychological therapy, occlusal therapy, physical therapy, cognitive therapy, acupuncture therapy, and surgical interventions. [1114] In cases of myofascial pain, strategies often target muscle relaxation. [5] Acupuncture is a commonly used strategy for pain relief in these cases, in which an acupuncture needle or, more often, multiple needles are inserted at the appropriate acupuncture points.…”
Section: Introductionmentioning
confidence: 99%
“…En el tratamiento de los trastornos temporomandibulares (TTMs) los resultados clínicos demuestran que el tratamiento por LBI es eficaz, siendo un método no invasivo indicado para el alivio del dolor agudo y especialmente del dolor miofascial crónico (Simunovic, 1996). Sin embargo, algunos investigadores señalan que el LBI presenta eficacia limitada en la reducción del dolor, no habiendo diferencias entre el grupo de pacientes con TTM tratados con LBI y el grupo placebo (Venancio et al, 2005;Emshoff et al, 2008;Chen et al, 2015).…”
Section: Introductionunclassified
“…Chen et al [41] in their meta-analysis (14 reports) concluded that R-NIR light therapy did not significantly reduce pain but did significantly improved the functional outcomes of patients with temporomandibular disorders (TMDs). Panhoca et al [42] showed that low-level R-NIR photo-stimulation can be useful in improving outcomes related to pain relief and mandibular range of motion for TMD patients, while de Castro et al [43] reported reduction of inflammatory infiltrate in the TMJ.…”
Section: Emission Spectrum Analysismentioning
confidence: 99%